Predation of common wall lizards: experiences from a study using scentless plasticine lizards - Jenő Purger; Zsófia Lanszki; Dávid Szép; Renáta Bocz (Acta Herpetologica, 2017)
The potential influence of predators on lacertid lizards has been studied by using models made of plasticine which shows the attack marks of predators and as such allows their identification and estimation of predation pressure. The general aim was to study predation on plasticine models of lizards and to improve methods, since the results depend on the number of plasticine models used, their spatial pattern and the duration of experiments. We estimated the density of the common wall lizard Podarcis muralis population on stone walls of a vineyard in the city of Pécs (Hungary) in August 2015 in order to imitate the real density in our experiment with plasticine models. The density of common wall lizards was 8.2 ind. /100 m2 and accordingly we placed 25 scentless plasticine lizards on the stone walls on the first transect with 10 m distance between them, which imitates the real pattern. In the second transect 25 lizard models were placed more sparsely, the distance between them being 20 m. During four weeks the predation rate was 24% in densely spaced plasticine lizards and 40% in sparsely spaced plasticine lizards, but the difference was not significant. The daily survival rate of densely spaced lizards was 0.99 (=99.1%) and that of sparsely spaced lizard models was 0.98 (=98.25%), but this difference was not significant either. On the basis of marks left on plasticine lizards, mammal predators (e.g. beech marten) dominated, while the impact of bird predators was smaller than expected. Predators attacked the head of plasticine lizards more frequently than their trunk, tail or limbs, but a significant preference of body parts was not detected. From our experience it is important to study the distribution and density of real animals, to imitate their real pattern, instead of an arbitrarily designed experiment with models. The typical scent of plasticine also could influence the results, which can be avoided by using scentless plasticine models coated with liquid rubber. We suggest the calculation of daily survival rates in order to produce results that allow the comparison of different studies.